2004
DOI: 10.1197/jamia.m1495
|View full text |Cite
|
Sign up to set email alerts
|

VA QUERI Informatics Paper: Information Technology for Clinical Guideline Implementation: Perceptions of Multidisciplinary Stakeholders

Abstract: Stakeholders share many concerns regarding the relationships between information technologies and clinical guideline use. However, administrators, physicians, and nurses hold different opinions about specific facilitators and barriers. Health professionals' disparate perceptions could undermine guideline initiatives. Implementation plans should specifically incorporate actions to address these barriers and enhance the facilitative aspects of information technologies in clinical practice guideline use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 23 publications
0
45
0
Order By: Relevance
“…Therefore, any IT implementation plans should address concerns of the stakeholders in order to build a better system. 35 …”
Section: Issues In It Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, any IT implementation plans should address concerns of the stakeholders in order to build a better system. 35 …”
Section: Issues In It Implementationmentioning
confidence: 99%
“…35,36 As IT becomes more integrated into the care delivery system, IT implementation is likely to expand to include other participants in the health care setting. The IT system needs to interface with, and be responsive to, patients, managers, providers, researchers, and the public.…”
Section: Issues In It Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, even when e-prescribing implementation is financially underwritten the perceived and real non-financial costs can cause failure. [2][3][4]6 However, the reporting of programs in Massachusetts 4 and New Jersey 3 that are piloting the apportionment of system-wide benefits to practices in the forms of implementation assistance are an encouraging connection of system-wide benefits to component parts (practices). Time is another important system consideration in HIT implementation.…”
mentioning
confidence: 99%
“…Similarly, in a large multisite focus group study of 18 medical centers, Lyons and colleagues demonstrated that different stakeholder groups hold different perceptions of the barriers and facilitators to using HIT to implement evidence-based practice. 6 Thus, an information system needs to be adapted during design, implementation, and ongoing maintenance to address the unique characteristics of the local context and continually assess and meet the needs of its providers, patients, and managers. Leu and colleagues created a series of process diagrams describing the clinical context in which HIT systems are used.…”
mentioning
confidence: 99%